Mitigation of Hepatic Impairment with Polysaccharides from Red Alga Albidum corallinum Supplementation through Promoting the Lipid Profile and Liver Homeostasis in Tebuconazole-Exposed Rats - Hajer Ben Saad; Donyez Frikha; Amir Bouallegue; Riadh Badraoui; Manel Mellouli; Hatem Kallel; Jean Marc Pujo; Ibtissem Ben Amara (MDPI AG, 2023)
Sulfated polysaccharides from seaweed are highly active natural substances with valuable applications. In the present paper, attempts have been made to discuss the physicochemical and structural features of polysaccharides isolated from red marine alga Alsidium corallinum (ACPs) and their protective effect in hepatic impairments induced by tebuconazole (TEB) in male adult rats. Structural features were determined using high-performance liquid chromatography, Fourier-transformed infrared, and solid-state 1H and 13C-Nuclear magnetic resonance analysis. ACPs are found to be hetero-sulfated-anionic polysaccharides that contain carbohydrates, sulfate groups, and uronic acids. In vitro biological activities suggested the effective antioxidant and antimicrobial capacities of ACPs. For antioxidant testing in vivo, the biochemical analysis and plasma profiles displayed that oral administration of ACPs could mitigate blood lipid indicators, including total cholesterol, triglyceride, low and high-density lipoprotein cholesterol, and bilirubin. Liver function indexes involving alanine aminotransferase and aspartate aminotransferase showed that ACPs possessed prominent antioxidant activities. Additionally, the intervention of ACPs potentially inhibited lipid peroxidation, protein oxidation, key enzymes of lipid metabolism (<0.001), and improved antioxidant status (<0.05). Histomorphological observation confirmed that ACPs intervention could partially repair liver injuries caused by TEB. The computational results showed that A. corallinum monosaccharides bound 1JIJ, 1HD2, and 1WL4 receptors with acceptable affinities, which, together with deep embedding and molecular interactions, support the antioxidant, antimicrobial, and hypolipidemic outlined effects in the in vitro and in vivo findings. Given their prominent antioxidant effects, ACPs are promising candidates for liver diseases and must be considered in pharmaceutical applications.